„ANDERE LÄNDER, ANDERE SITTEN“: A COMPARATIVE STUDY OF SOME GERMAN AND INDONESIAN PROVERBS - Rikfanto, Aditya (Proverbium - Yearbook, 2023)
Apart from their status as a cultural heritage that remains relevant at all times, some German proverbs also have comparable messages to Indonesian proverbs. Therefore, this study aims to compare some German and Indonesian proverbs in terms of pragmatics and semantics with the thematic delineation of customs and cultural norms. Baseline data for this study comes from the online corpus of the OWID Leibniz Institute and a concise German-Indonesian proverb dictionary. In addition, this research also applies the Google Scholar search function to determine how often proverbial texts appear in scientific literature. The results show that German proverbs referring to customs frequently appear in various academic contexts: „Andere Länder, andere Sitten“ (Other countries, other customs). This proverb is also comparable to an Indonesian proverb with the same theme. However, the semantic and pragmatic features of each proverb appeared differently. The German proverb tends to present the denotative statement without metaphorical abstraction, but it appears elliptical. The Indonesian proverb "Di mana Bumi dipijak, di situ langit dijunjung" (Where the Earth is trodden, there the sky is upheld) is somewhat metaphorical. At the same time, the elliptical structure does not appear.